Synthesis and Characterization of Zeolite A from Industrial Fly Ash as a Green, Cost-Effective Cd2+ and Pb2+ Adsorbent for Wastewater Applications - Darunee Sukchit; Malee Prajuabsuk; Saisamorn Lumlong; Chan Inntam; Auradee Punkvang; Sasijuta Wattanarach; Parjaree Thavorniti; Bunjerd Jongsomjit; Kanitta Wongyai; Duangkamol Gleeson; Paramasivam Shanmugam; Supakorn Boonyuen; et al. (My University, 2025)
According to the large amount of fly ash waste generated from the use of lignite coal as the primary fuel for electricity generation in the Mae Moh district of Lampang province, Thailand, efforts have been made in waste management to reduce and repurpose this industrial byproduct. In this study, lignite coal fly ash was used to synthesize zeolite A adsorbents for the treatment of wastewater contaminated with heavy metals. Characterization of the synthesized zeolite using XRD, XRF, BET, and SEM methods confirmed that it is zeolite A, with a calculated Si/Al molar ratio of approximately 1.19, closely matching the theoretical ratio of zeolite A. This zeolite A exhibited a high crystalline phase and a mesoporous structure, having a specific surface area of 37.10 m2/g and a total pore volume of 0.06 cm3/g. The performance of this zeolite A was evaluated for the adsorption of Cd2+ and Pb2+ in prepared solutions. The removal efficiencies of zeolite A for Cd2+ and Pb2+ were 99.65% ± 0.1% and 93.90% ± 0.5%, with maximum adsorption capacities of 17.3 ± 0.6 and 8.8 ± 0.1 mg/g, respectively. Additionally, zeolite A demonstrated reusability for the adsorption of Cd2+ and Pb2+, maintaining a removal efficiency of 80.52% ± 0.1% for Cd2+ over five reuse cycles, and 96.83% ± 0.7% for Pb2+ over one reuse cycle. The adsorption of Cd2+ and Pb2+ by zeolite A followed the Langmuir isotherm model and pseudo-second-order kinetic model. Moreover, the adsorption of Cd2+ and Pb2+ by zeolite A was found to be a spontaneous, endothermic process, as evidenced by increasingly negative Gibbs free energy change (ΔG°) values with rising temperature. Density functional theory (DFT) calculations were also performed to investigate the binding of Cd2+ and Pb2+ ions to zeolite A, providing insight into why Cd2+ exhibits a slightly higher affinity than Pb2+. The results showed that Cd2+ ions have a marginally greater affinity for zeolite A compared to Pb2+ (-85.72 vs -85.39 kcal/mol), which aligns with experimental findings. This study offers an alternative approach for reducing industrial waste by repurposing it for valuable applications, contributing to sustainable waste management practices that align with the principles of the bio-circular-green economy.
Keywords: Characterization; Adsorption and biosorption for pollutant removal